Penerapan Program Kegiatan Kampus Mengajar Untuk Meningkatkan Karakter Bangsa pada Siswa di UPT SD 060916 Medan Sunggal - Zihan Amira Shandra; Belianti, Belianti (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
The teaching campus program is motivated by Indonesia currently in need of student assistance to help teachers and younger elementary school students to get more optimal learning opportunities.  Students can develop their abilities, especially in terms of creativity, leadership, and other interpersonal skills through the experience of the Teaching Campus program.  This Mini Project activity was carried out at UPT SD 060916 Medan City, Sunggal.  The lack of national character education will certainly cause a moral crisis such as social problems in society, brawls between students, drug abuse, drinking, and other things that do not reflect the national character of students.  The real form of this Mini Project is to provide education to UPT SD 060916 students about the importance of improving national character.  The method used in carrying out this mini project activity is to use the casework method through the Intervention stage in general which consists of Engagement, Intake, Contract, Assessment, Planning/Planning, Intervention, Evaluation and Termination.  As a result of this mini project activity, UPT SD Negeri 060916 students already understand the importance of improving national character so that it can be applied in everyday life until adulthood.